Education and training methods for healthcare professionals to lead conversations concerning deceased organ donation: An integrative review - Potter, J.E.; Elliott, R.M.; Kelly, Michelle; Perry, L. (2021)
Objectives: To determine which training methods positively influenced healthcare professionals’ communication skills and families’ deceased organ donation decision-making.